Música, Informação e Identidade nas obras de waldemar henrique - ALVES, Namara Nayane de Souza (2019)
This research is about music, identity and information in Waldemar Henrique’s works. It studies the terms present in the lyrics of seven songs of the conductor that have as subject the Amazon legends. It adopts a qualitative approach using bibliographical and documentary research. The songs that form the corpus of the study are analyzed as a source of information about Amazonian identity and culture. In his songs, Waldemar Henrique assumes the role of narrator to communicate to the reader / listener information about a place with which he has identified and known since childhood. The research concludes that the terms in the songs speak about legends, flora, fauna, customs, ways of speaking and being that refer to the populations living in the Brazilian Amazon, especially in the countryside and in the areas near the rivers.